A NEW RECORD OF THE CREEPING CUCUMBER, Melothria pendula L. (Cucurbitaceae) FROM HALMAHERA, NORTH MALUKU, INDONESIA - Deby Arifiani; Lulut Dwi Sulistyaningsih; Rugayah Rugayah; Deni Sahroni (BIOTROPIA, 2024)
Article Highlights- Botanical inventory in Halmahera island, North Maluku has found the species Melothria pendula for the first time.- In Indonesia, the species Melothria pendula is previously known only from Java, Sumatra, Sulawesi, and Lesser Sunda Island.- DNA barcodes for the species Melothria pendula from Indonesia firstly deposited in NCBI GenBank. AbstractThis study was conducted to explore Melothria pendula on Halmahera Island. Previously, the species is known to occur in Bali, Sulawesi, Sumatra, Java (Indonesia), Malay Peninsula, Sabah (Malaysia), as well as the Philippines. Results of this study improved insights into the current knowledge about geographic distribution of Melothria. Moreover, the description of the species, habitat, critical taxonomic notes, color plates, distribution map, and DNA barcode were also presented in this study.